PATH ANALYSIS OF FACTORS AFFECTING STRESS, ANXIETY AND DEPRESSION IN MEDICAL RESIDENTS DURING THE COVID-19 PANDEMIC - Karima, Aziza Matinu; Maharatih, Gusti Ayu; Nugroho, I Gusti Bagus Indro (Journal of Psychiatry Psychology and Behavioral Research, 2026)
Introduction: The COVID-19 pandemic has significantly affected the mental health of medical personnel, particularly residents who face high clinical workloads, exposure risks, and academic pressures. The aim of this research to analyze direct and indirect determinants of stress, anxiety, and depression among medical residents using path analysis. Methods: A cross-sectional study involving 437 residents at Dr. Moewardi Hospital was conducted in October–November 2020. Stress, anxiety, and depression were assessed using the DASS-21, while coping mechanisms were measured using the Brief COPE. Data analysis was conducted using path analysis. Results: Stress (β = 0.5; p < 0.001) and anxiety (β = 0.18; p < 0.001) directly increased depression, while adaptive coping showed a negative association (β = –1.2; p < 0.001). Age, sex, comorbidities, and COVID-19 exposure had indirect effects mediated by stress and anxiety. Discuss: The findings of this study underscore the importance of interventions that reinforce adaptive coping, including stress management training, mindfulness, peer support, and religious approaches. Conclusion: Stress and anxiety significantly predicted depression, while adaptive coping had a protective effect.  Keywords: stress, anxiety, depression, coping, medical residents, COVID-19.